Increase in humidity widens heat tolerance range of tropical Ceratosolen fig wasps. (25th December 2020) - Gigante, Earl Terrenz; Lim, Emmanuel Justin; Crisostomo, Kei Gabrielle; Cornejo, Patricia; Rodriguez, Lillian Jennifer
Abstract : 1. Fig wasps are the obligate mutualistic pollinators of fig trees, which are important components of tropical forests. The stability of these species interactions, in the face of environmental changes, relies heavily on the thermal tolerance of these wasps. 2. This study determined the upper thermal limits of three tropical Ceratosolen fig wasp species. Humidity levels and collection season were varied to determine the effect of water availability on heat tolerance. 3. Wasps were placed in incubators to simulate different temperature regimes (30–45 °C) with varying humidity conditions. Wasp populations from either the dry or wet seasons were tested. Upper lethal temperature was determined by recording wasp survival. 4. All factors (temperature, humidity, season, wasp species, and their interactions) significantly affected wasp longevity. Exposure to high temperatures resulted in a significant decrease in wasp longevity: longest at 30 °C and the ratio decreased rapidly at 40 and 45 °C. An increase in temperature from 30 to 35 °C caused at least a two‐fold reduction in wasp lifespan. More surprisingly, humid conditions allowed survival for two to six times longer than non‐humid conditions in high temperatures (40–45 °C). Wasps obtained during the wet season also survived longer than those from the dry season. Increased water availability (i.e. during wet season and with high humidity conditions) thus increased wasp upper thermal limits. 5. Relative humidity was a strong limiting factor in the heat tolerance of tropical wasps. Persistence of insect species that are narrowly‐distributed will depend on the presence of intact, high‐humidity habitats. Abstract : Increase in relative humidity consistently lengthened the lifespan of Ceratosolen species across different temperature and seasonal conditions. Temperature response of all three Ceratosolen species was strongly dependent on the season, with wasps from the wet season having significantly longer lifespan than those from the dry season. Increased water availability (i.e. during wet season and with high humidity conditions) increased wasp upper thermal limits.